Extraordinary Experiences and Religious Beliefs - Shushan, Gregory (Method & theory in the study of religion, 2014)
Many contemporary scholars believe that all experience is dependent upon language and culture, meaning that it is unintelligible to speak of some cross-cultural event which can be called “mystical” or “religious”; and that the notion of the origins of religious beliefs lying in such experiences is thus methodologically and theoretically unsound. Challenges to these perspectives leave one open to charges of naivety, or of having crossed a boundary from the (ostensibly) objective Study of Religions into a kind of universalist crypto-theology. In defense of the study of such experiences, this article attempts to demonstrate the weaknesses in these arguments by showing that they are based upon a number of mutually-reliant but unproven culturally-situated philosophical axioms. With particular reference to near-death and out-of-body experiences, a reflexive, theoretically eclectic approach to this area of study is suggested.